The Application of Character Education in the Family Environment during the COVID-19 Pandemic - Rina Nur Bashiroh; Erni Munastiwi; Silva Ardiyanti; Lely Masruroh (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
Character education is considered as education of human morality values ​​which is based on and carried out in real action. There is an element of value formation and attitude based on knowledge to do so. This value is a value that can help better interaction with other people. This value includes various areas of life, for example vertical relationships with God, human relations, relationships with oneself, relationships with the environment, and the state. This study aims to shape the character of children in the family environment in the era of the Covid-19 pandemic that is currently being faced. This is to find out the level of creativity of parents in applying the values ​​of character education in the family environment, to shape children into children with good morals. This study used a qualitative method with one research subject, which was then analyzed using the description of sentences and the results of the research subject, namely interviews. The results of this study are character education that is implemented in the family environment by disciplining children in their work, starting from cleaning the surrounding environment to applying the value of children's responsibility to themselves, especially adolescents who are actually still looking for an identity, and parents train children to become children who independently